Navigating the unknown: how to best ‘reflect’ standard of care in indications without a dedicated treatment pathway in health technology assessment submissions - Grammati Sarri; Maria Rizzo; Sheela Upadhyaya; Victoria Federico Paly; Luis Hernandez (Journal of Comparative Effectiveness Research, 2024)
There is an urgent need for expedited approval and access for new health technologies targeting rare and very rare diseases, some of which are associated with high unmet treatment needs. Once a new technology achieves regulatory approval, the technology needs to be assessed by health technology assessment (HTA) bodies to inform coverage and reimbursement decisions. This assessment quantitatively examines the clinical effectiveness, safety and/or economic impact of the new technology relative to standard of care (SoC) in a specific market. However, in rare and very rare diseases, the patient populations are small and there is often no established treatment pathway available to define ‘SoC’. In these situations, several challenges arise to assess the added benefit of a new technology – both clinically and economically – due to lack of established SoC to guide an appropriate comparator selection. These challenges include: How should ‘SoC’ be defined and characterized in HTA submissions for new technologies aiming to establish new treatment standards? What is usual care without an established clinical pathway? How should the evidence for the comparator ‘SoC’ (i.e., usual care) arm be collected in situations with low patient representation and, sometimes, limited disease-specific clinical knowledge in certain geographies? This commentary outlines the evidence generation challenges in designing clinical comparative effectiveness for a new technology when there is a lack of established SoC. The commentary also proposes considerations to facilitate the reliable integration of real-world evidence into HTA and decision-making based on the collective experience of the authors.